What happens to children's education when their parents emigrate? Evidence from Sri Lanka. (January 2016) - Sarma, Vengadeshvaran J.; Parinduri, Rasyad A.
Highlights: We estimate the effect of parental migration on their children's education. On average, parental migration has no statistically significant effect on children's education. The effects are however statistically significant and opposing when analysed by gender of the migrant parent. Boys, younger children, and children of the less educated parents gain more from parental migration. Abstract: We examined the effects of parental emigration on the education of the children left behind in Sri Lanka. Using access to foreign employment agencies as a source of exogenous variation in parental migration, we estimated two-stage least squares models of the children's school enrolment, access to private tuition, class-age gap (the difference between a child's school year and the child's age), and educational spending. Overall, parental migration had no statistically significant effect on any of the outcomes; however, analyses by migrant gender show that the effects of parental migration were heterogeneous. When the mother migrates and the father stays behind, the education of the children worsens; when the father migrates and the mother stays behind, it improves. There is also some evidence that boys, younger children, and children of less-educated parents gain more from parental migration.